A constraint model for assembly planning. (January 2020) - Kardos, Csaba; Kovács, András; Váncza, József
Highlights: Assembly sequencing and resource assignment Integrated planning workflow Constraint model for macro planning Arbitrary liaison graphs Feasibility cuts for micro level feedback Three industrial use-cases Abstract: The importance of computer-aided process planning (CAPP) for assembly is widely recognized, as it holds the promise of efficient and automated construction of solutions for a complex, geometrically, technologically, and economically constrained planning problem. This complexity led to the introduction of decomposition approaches, separating the macro-level planning problem that oversees the complete assembly process from the various micro-level problems that look into the details of individual assembly operations. The paper introduces a constraint model for solving the macro-level assembly planning problem based on a generic feature-based representation of the product and the assembly operations involved. Special attention is given to capturing the feedback from micro-level planners expressed in the form of feasibility cuts, and hence, to the integration of the approach into a complete CAPP workflow. Results on three case studies from different industries are also presented to illustrate the practical applicability of the approach.